From the regulatory aspects to existing practices of restorative justice: the experience in Switzerland - Annamaria Astrologo (Droit et Cultures)
The aim of this paper is to reconstruct the Swiss regulatory context in which the introduction of an ad hoc discipline for restorative justice is planned. To date, in fact, there are still few rules which, in a manner that is fragmentary and not always consistent with the rationale of restorative justice, may appear to be rather weak links to this approach. Nonetheless, in practice, experiments of restorative justice practices are gaining a space for themselves which, even in the absence of a defined regulatory perimeter, support the people involved in a criminal offence towards a recomposition with themselves and the other people.